2022
DOI: 10.3389/fphar.2022.1031910
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the benefits of TNF-alfa inhibitor biosimilar competition on off-patent and on-patent drug markets: A Southern European analysis

Abstract: Background: The level of competition achieved following biosimilars market availability varies by country, care setting and molecule. Hence, biosimilars contribution to attaining price reductions and extended access to treatments can also vary.Objective: The aim of this study is to capture market dynamics for tumor necrosis factor (TNF)-alpha inhibitors and competing molecules in Southern European markets (2011–2020), and to evaluate the benefits of the competition generated by the availability of biosimilars.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Additionally, the price of the originator significantly decreased, by 89% in the Netherlands and by 80% in the EU tender market, to stave off the use of biosimilars [ 34 , 35 ]. Biosimilar competition has also led to considerable price reductions in Denmark, England, and southern European countries, such as in Italy, Portugal, and Spain [ 31 – 33 ]. The more price reductions, the greater the potential cost savings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the price of the originator significantly decreased, by 89% in the Netherlands and by 80% in the EU tender market, to stave off the use of biosimilars [ 34 , 35 ]. Biosimilar competition has also led to considerable price reductions in Denmark, England, and southern European countries, such as in Italy, Portugal, and Spain [ 31 – 33 ]. The more price reductions, the greater the potential cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…Barcina Lacosta et al, identified that the introduction of TNF-α inhibitor biosimilars (those for infliximab, etanercept, and adalimumab) resulted in cost savings despite similar or increased consumption in Southern European countries like Italy, Portugal, and Spain. They also observed heterogeneous utilization of biosimilars in Italy and Spain, which could be associated with the decentralized healthcare systems [ 31 ]. Vogler and colleagues highlighted that the policies to encourage the use of biosimilars in European countries have clearly demonstrated potential savings [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In countries where biosimilar or reference drug use is obligatory and fixed in a tender, various approaches for introducing a new agent exist [ 19 , 21 , 29 , 30 ]. Regional- and nation-wide strategies include a mandate of the selected agent for all or only for new patients.…”
Section: Discussionmentioning
confidence: 99%
“…In order to encourage wider uptake of biosimilars, various countries are implementing different incentive systems [ 19 , 33 36 ]. Studies from various European countries, including Poland, show that the share of off-patent drugs is steadily decreasing, at the expense of more modern on-patent therapies [ 10 , 21 , 22 , 30 ]. While selecting the cheapest drug from the off-patent group guarantees its market share, there is no priority over other on-patent drugs, often with different modes of action.…”
Section: Discussionmentioning
confidence: 99%